Durability of polyester polymer concretes based on metallurgical wastes for the manufacture of construction and building products. (20th April 2020) - Seco, A.; Echeverría, A.M.; Marcelino, S.; García, B.; Espuelas, S.
Highlights: Metallurgical wastes can substitute of natural aggregates in the polymer concretes. The chemical resistance depended on the target material used. Metallurgical wastes showed a good resistance against the chemical substances. Ladle slag showed the best mechanical strength and surface strength against impacts. The surface resistance against scratching depended on the resin. Abstract: Varied target materials can be incorporated into polyester polymer concretes (PPC). This allows natural aggregates to be substituted for different waste products in non-structural polymeric construction and building materials. Many studies have explored the mechanical properties of waste-based PPC, but the durability and surface resistance of these materials is not fully known. In this study, we compared the suitability of two metallurgical wastes to that of two natural aggregates for manufacturing durable PPC products. Durability against environmental conditions, durability against chemical products, and surface strength against physical damage were tested. Durability against environmental conditions was characterised according to visual damage and mechanical strength losses after freezing-thawing; no PPC combinations exhibited surface damage following the ageing cycles. The ladle slag (LS) samples exhibited the best pre- and post-test flexural and compressive strength. The properties of the alumina filler (AF) combinations exhibited the highest flexural and compressive strength losses after freezing-thawing. The calcareous sand combinations were damaged most severely by acid, while LS and AF exhibited good resistance against chemical substances. The LS combinations exhibited the highest surface strength against impacts in the rebound number test, while the results obtained for the AF combinations were close to those of natural aggregates. The surface resistance against scratching depended on the resin, not on the target material.